(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
In their daily interaction with students, teachers can work to promote students’ social skills and prevent behaviour problems. An evaluation was conducted on the impact of the Incredible years teacher classroom management universal intervention program, and six female teachers from three preschool education facilities took part in the evaluation. The evaluation instruments used were: (a) Best practices inventory (Vale, 2011), (b) Preschool social behaviours scale (Merrell, 2002), (c) Workshop evaluation questionnaire (Webster-Stratton, 2012), (d) Program evaluation questionnaire (Webster-Stratton, 2012), and (e) the IY TCM program (Webster-Stratton, 2012). Significant differences were found between pre-test and post-test (p < 0.05) both in relation to the participants’ classroom management strategies and also the children’s social skills and behaviour problems. The IY TCM program demonstrated strong positive scientific evidence of strengthening and promoting child development protection factors among the preschool teachers.